Identification of genes related to resin biosynthesis in the Indian lac insect, Kerria lacca (Hemiptera: Tachardiidae). (29th May 2014) - Shamim, Gulsaz; Pandey, D.M.; Ramani, R.; Sharma, K.K.
<x content-type="archive" xml:space="preserve">Abstract</x> Kerria lacca (Kerr) is commercially harnessed for lac resin, which is principally an ester complex of aleuritic acid (9, 10, 16-trihydroxyhexadecanoic acid) and jalaric acid. The present study is an attempt made to identify the possible pathways involved in the biosynthesis of lac resin. It is proposed that acetyl-CoA is the common precursor for the biosynthesis of aleuritic acid and sesquiterpenic acids (jalaric acid). Prenyltransferases are involved in the biosynthesis of sesquiterpenes; hydroxylation of hexadecanoic acid, after chain elongation, appears to occur through the action of cytochrome P450 enzymes. Two related genes as proposed above were identified and sequenced. The diurnal rhythm of resin secretion and protein concentrations were also studied and correlated for ascertaining the active secretory phase.